Re-reading the “Classics”: Thucydides and Political Realism - T. A. Alekseeva (Сравнительная политика)
The theme of the article – a widely spread appealing to Thucydides and his famous “History of the Peloponnesian War” as some sort of the “sanctions” for scientific respectability of the theoretical studies of international relations. Such an attitude was formed under the influence of Thomas Hobbes and later supported by “political realism” as one of the most popular paradigms in the theory of international relations. The “interpretation of the interpretations” demonstrates, that the texts of Thucydides are often badly read and not always rightly understood, his conclusions are eradicated out of context, and they got too extended interpretation. The result many of his ideas are oversimplified or even misrepresented or distorted. From our point of view, the “classics” deserve a more cautious attitude, and the quoting of their works ought to be more weighted and thought of, at the very least nor to be automatic.